Influence of the Sample Radius and Irradiated Zone Width on the Defocusing Phenomenon in the Schulz Technique - Hermida, Jorge Daniel (Elsevier, 1982)
Fil: Hermida, Jorge Daniel Comisión Nacional de Energía Atómica; Argentina